(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Suppurative chondritis of auricle due to burn injury is a devastating complication which usually results in deformed shrunken ugly ear in spite of many modalities for treatment. Objectives:To document clinical nature of the injury, the results of various methods of treatment, and to recommend the management protocol of chondritis of burned ear. Methods:From Nov. 1998 to Nov. 2010 a prospective study performed on 100 patients 110 ears in Hilla Teaching General Hospital, Al-Kindy Teaching General Hospital on surgical treatment of suppurative chondritis. All cases were due to flame burn, and all were given prophylactic systemic antibiotics. Results:Forty six of patients were males (46%), 54 females (54%), ages ranged from 1 year 35 years with mean 24years, partial thickness burn 80 patients (80%), full thickness burn 20 patients (20%) . Patients treated in three groups; the first group 20 ear (18%), treated by only stab wound drainage which resulted in 100% recurrence, the second group 20 ears (18%) treated by limited wound excision which resulted in 85% recurrence, the third group 70 ears (64%) treated by radical wound excision which resulted in 10% recurrence, total loss of auricle occurred in 10%, moderate deformity occurred in 80% of ears, mild deformity resulted in 10% of ears. Conclusion:Surgical treatment of Suppurative chondritis gives superior results by radical excision. Key words: Chondritis, Suppurative chondritis, Burned ears, Radical chondrectomy, Deformed ear.